Recreational trails are an important cause of fragmentation in endangered urban forests: A case-study from Australia - Ballantyne, M.; Gudes, Ori; Pickering, C. (Elsevier BV, 2014)
Remnant urban forests are often popular sites for recreational activities such as hiking, biking and motorised recreation. This can result in the formation of extensive trail networks, fragmenting vegetation into patches separated by modified edge effects and ultimately contributing to the degradation of the ecosystem as a whole. Here we use a GIS approach to assess the extent and diversity of trail-based fragmentation across 17 remnants of endangered urban forest (total area 829 ha, Tall Open Blackbutt Forest) in southeast Queensland, Australia. Fourteen different trail types totalling 46.1 km were mapped with informal biking and hiking trails the most common (57%, 26.5 km). More than 47 ha (5.7%) of forest have been lost to trails and their edge effect, nearly equal to the area recently cleared for urban development. The degree of fragmentation in some remnants was in the same order of magnitude as found for some of the most popular nature-based recreation sites in the world. In localised areas, the fragmentation was particularly severe as a result of wide trails used by motorised recreation, but these trails were generally uncommon across the landscape (5%). Spatial regression revealed that the number of access points per remnant was positively correlated with the degree of fragmentation. We encourage more landscape-scale research into trail-based fragmentation due to its capacity to impact extensive areas of endangered ecosystems. Management should seek to minimise the creation of informal trails by hardening popular routes, instigating stakeholder collaboration and centralising visitor flow.